An Exploration of New Product Physical Attributes and Consumer Variety-Seeking In the Mobile Phone Category - Yeboah, Abraham; Adjei; Vida Owusu-Prempeh, Samuel (British Journal of Marketing Studies, 2018)
The consumer switching from one brand to the other brand is more intense across global markets in both physical in-store and webstore buying decision making. The consumer brand switching has made it difficult for marketing and sales practitioners, shop owners and portfolio managers to develop specific programmes to meet market demand. In order to uncover aspect of the variety-seeking behaviour, the study introduced optimal level theories (optimal stimulation level) with the much focused on the cognitive structure. The aim of this research is to explore new product physical attributes and consumer variety-seeking in the mobile phone category. The study mainly assessed product typography, product colour, product texture, and product shape. A sample of 133 respondents was employed using convenient selection method. A self-completed 5 point Likert structured questionnaire survey was the data collection instrument used. The data collected were computed and analysed by the use of Cramer’s V under crosstabulation statistics, which takes into account the degrees of freedom in measuring the association. On the whole, the study found weak association between new product physical attributes and consumer variety-seeking in the mobile phone category. Again findings show that, product typography, product colour, product texture and product shape and consumer variety-seeking reveals weak association. Further study can look into non-cognitive dimension of product attributes to ascertain importance its play towards variety-seeking behaviour.